2010
DOI: 10.1038/npp.2009.230
|View full text |Cite
|
Sign up to set email alerts
|

Differential Association of Circadian Genes with Mood Disorders: CRY1 and NPAS2 are Associated with Unipolar Major Depression and CLOCK and VIP with Bipolar Disorder

Abstract: Disruptions in circadian rhythms have been described in mood disorders (MD), but the involvement of genetic variation in genes pertaining to the molecular circadian machinery in the susceptibility to MD has not been conclusively determined. We examined 209 single-nucleotide polymorphisms (SNPs) covering 19 circadian genes (ADCYAP1, ARNTL, ARNTL2, BHLHB2, BHLHB3, CLOCK, CRY1, CRY2, CSNK1E, DBP, NPAS2, NR1D1, PER1, PER2, PER3, RORA, TIMELESS, VIP, and VIPR2) in a sample of 534 MD patients (335 with unipolar majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
206
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(212 citation statements)
references
References 95 publications
5
206
0
1
Order By: Relevance
“…On the other hand, two lines of evidence suggest a link: the association of polymorphisms of some circadian genes and features of depression (such as age at onset, diurnal activity pattern, insomnia) and the effects of antidepressant medications on circadian gene expression. A recent study suggested an association between haplotypes in the cry1 and npas2 genes and unipolar major depression [16]. This study provides some support for the involvement of the circadian system with depression, suggesting that variations may, at least, represent a vulnerability factor(s) for the disorder.…”
Section: Circadian Rhythms and Depressionsupporting
confidence: 62%
“…On the other hand, two lines of evidence suggest a link: the association of polymorphisms of some circadian genes and features of depression (such as age at onset, diurnal activity pattern, insomnia) and the effects of antidepressant medications on circadian gene expression. A recent study suggested an association between haplotypes in the cry1 and npas2 genes and unipolar major depression [16]. This study provides some support for the involvement of the circadian system with depression, suggesting that variations may, at least, represent a vulnerability factor(s) for the disorder.…”
Section: Circadian Rhythms and Depressionsupporting
confidence: 62%
“…Of note, adult ADHD is linked with blunted Per2 expression (Baird et al, 2012). It is also interesting that the other clock genes with altered circadian profiles in ENT1 KO mice, Clock and Dbp, are associated with ADHD (Kissling et al, 2008;Roybal et al, 2007;Xu et al, 2010), bipolar disorder (Le-Niculescu et al, 2008;Lee et al, 2010;Shi et al, 2008;Soria et al, 2010), anxiety (Le-Niculescu et al, 2011a), and AUD (Le-Niculescu et al, 2011b;Le-Niculescu et al, 2008). Interestingly, ENT1 KO mice display mania-like behavior (Ruby et al, 2011) similar to Dbp KO mice (Le-Niculescu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Genes reloj que también se hallan implicados en diversos problemas de salud mental. En los trastornos depresivos existen asociaciones con polimorfismos en los genes Per2 (Lavebratt, Sjöholm, Partonen, Schalling y Forsell, 2010), Per3 (Nievergelt et al, 2006) y Clock (Benedetti et al, 2003), en el trastorno bipolar destacan los polimorfismos en los genes Per3 (Nievergelt et al, 2006) y Clock (Soria et al, 2010) , en el consumo de drogas se han hallado relaciones con los genes Per1 (Liu et al, 2007;McClung, 2007), Per2 (Perreau-Lenz, Zghould, de Fonseca, Spanagel y Bilbao, 2009) y Clock (McClung, Sidiripoulou, Vitaterna, Takahashi y White, 2005), y la esquizofrenia se ha visto asociada a polimorfismos de los genes Per3 (Mansour et al, 2006) y Clock (Zhang et al, 2011). Por último, los trastornos de sueño se anales de psicología, 2014, vol.…”
Section: Discussionunclassified